Clinical experience with adaptive MRI-guided pancreatic SBRT and the use of abdominal compression to reduce treatment volume - Ferris, William S.; George, Benjamin; Plichta, Kristin A.; Caster, Joseph M.; Hyer, Daniel E.; Smith, Blake R.; St-Aubin, Joel J. (Frontiers in Oncology, 2024)
Introduction: This work presents a method to treat Stereotactic Body Radiation Therapy (SBRT) for pancreatic cancer on an MR-linac, using daily adaptation, real-time motion monitoring, and abdominal compression. Methods: The motion management and treatment planning process involves an MRI simulation with cine and 3D images, a computed tomography (CT) simulation with a breathhold CT and a 4DCT, pre-treatment verification and planning magnetic resonance imaging (MRI), and intrafraction MRI cine images. Results: The results from 26 patients were included in this work. Our motion management process results in consistent motion analyzed on the CT simulation, MRI simulation, and each treatment fraction. The liver dome was found to be an overestimate of tumor superior/inferior (SI) motion for most patients. Adding compression reduced SI liver dome motion by 6.2 mm on average. Clinical outcomes are similar to those observed in the literature. Conclusions: In this work we demonstrate how pancreatic SBRT can be successfully treated on an MR-linac using abdominal compression. This allows for an increased duty cycle compared to gating and/or breathhold techniques.